MENINGKATKAN TANGGUNG JAWAB SISWA TERHADAP PERATURAN SEKOLAH MELALUI LAYANAN KONSELING KELOMPOK - Ulina, Risma (Universitas Islam Negeri (UIN) Sumatera Utara, 2023)
Student responsibility for school regulations is a reflection of students who are disciplined and have character. To form this attitude and responsibility requires an example and habituation that starts from the environment around him. The most effective way to train students to be responsible is to provide group counseling services, namely as a group training students to be brave and able to interact with fellow group members so that individuals who have weak points can be overcome and become responsible individuals by discussing problems together with the group. through group dynamics. The formulation of the problem in this research is how group counseling can increase students' responsibility for school regulations in class The aim of this research is to find out whether group counseling services can increase students' responsibility towards school regulations. To see the aspect of responsibility towards school regulations as a KKp participant, researchers determined eight aspects of indicators of student responsibility towards school regulations. Progress is monitored at each activity stage of implementing group counseling services which includes the formation stage, transition stage, activities and termination or closing stage. Of the eight indicators determined, overall students can achieve improvement as seen by changes in cycle I to cycle II, if averaged in cycle I, the percentage obtained is 30% in KKp 1, increasing to 50% in KKp 2 and increasing again in cycle II starting from KKp 1 amounted to 72.5% and the increase increased to KKp 2 amounting to 92.5%. In this way, group counseling services can increase students' responsibility for school regulations, meaning that the research hypothesis is accepted.